The role of telomeres in leukemic stem cells function - Raheleh Farahzadi; Behnaz Valipour; Ezzatollah Fathi; Sakhavat Abolhasani (Regenerative Therapy, 2025)
The length of a telomere provides insight into the replication history of a cell. Notwithstanding the fact that the telomerase enzyme is produced by stem and progenitor cells, a considerable proportion of the documented telomere degradation takes place at these levels. Sequential transplantation remains a challenge for hematopoietic stem cells (HSCs) transfected with telomerase, despite their ability to maintain telomere length. To optimize stem cell proliferation, additional parameters must be considered [1]. In contrast, unregulated telomere depletion induced by HSCs appears to play a significant role in the pathogenesis of bone marrow failure, as demonstrated by dyskeratosis congenita. It implies that telomerase dysfunction serves as a prevalent ultimate pathogenic mechanism in this heterogeneous hereditary disorder. Although this condition is not well defined, acquired marrow failure syndromes have been linked to mutations in critical telomerase components. In light of the discovery of leukemic stem cells (LSCs) and the desire to develop anti-leukemia treatments for this population, a comprehensive understanding of the telomerase biology within this cell compartment is required. Further research must employ LSC-rich primary samples that have been selected. A more thorough understanding of the correlation between telomere length and telomerase regulation in this specific population may facilitate the creation of innovative approaches or small molecule inhibitors that specifically target the telomerase enzyme complex.